AIDS Awareness and Educating Adolescents about Contraception Techniques: A Sociological Study of Parents and Teachers - Singh, Amanpreet (Dhaulagiri Journal of Sociology and Anthropology, 2011)
This paper is based on partially exploratory and partially descriptive research design to find out AIDS awareness and agreement of parents and teachers on educating adolescents about contraception techniques. For this study 60 parents and 60 teachers were interviewed from 10 different Govt. Senior Secondary schools in district Sangrur, Punjab, India. The random sampling technique was used. The knowledge of AIDS among parents was found partial. Mothers showed lesser knowledge of AIDS in comparison to fathers. Teachers showed comprehensive knowledge of AIDS. Majority of respondents disagree on educating adolescents about contraception techniques. But all responded reported to be in agreement to provide full knowledge about AIDS to adolescents. The education of contraception for adolescent found to be associated with the knowledge of prevention from unwanted pregnancy. Parents and teachers showed propensity to provide such education to adolescents which advocates sexual abstinence until marriage. The plausible reason to such perception could be that in most of Indian societies there is taboo on sex or sex related discussion. Keywords: Adolescents and AIDS; contraception knowledge to adolescents; teachers and AIDS; parents and AIDS DOI: 10.3126/dsaj.v4i0.4520 Dhaulagiri Journal of Sociology and Anthropology Vol.4 2010 pp.193-210